ANALSIS KOMPARASI KINERJA KEUANGAN BANK MEGA SYARIAH MENGGUNAKAN METODE RGEC PADA MASA SEBELUM DAN SELAMA PANDEMI COVID-19 - Azizoma, Rusman; Maulida, Fauzia Nindita (Institut Agama Islam Negeri (IAIN) Ternate, 2024)
The COVID-19 pandemic has had an impact on all industrial sectors in Indonesia, one of which is the sharia banking sector. During the pandemic, banking performance experienced fluctuations in terms of deposits and debt financing; Bank Mega Syariah also experienced fluctuations in financial ratios and deposits, which could have an impact on the bank's financial performance. The purpose of this study is to evaluate Bank Mega Syariah's financial results utilizing the RGEC approach both before and after the COVID-19 epidemic. This study used quantitative research using a descriptive methodology. Data was acquired through the use of documentation methods. Financial ratio analysis utilizing the RGEC method is the data analysis method employed. The findings demonstrate that Bank Mega Syariah's financial performance, as measured by the RGEC technique, was superior to its pre-COVID-19 pandemic financial performance during the pandemic-affected period. This is shown by Bank Mega Syariah's ability to continue turning in a profit despite the COVID-19 pandemic's negative impact on the business environment. This accomplishment is demonstrated by the growth in several key business metrics, which were maintained, including bank profitability, finance distribution, and Third Party Funds.Keywords: Financial Performance; Bank Health Level; RGEC Method